Esketamine Optimized the Efficacy of Dexmedetomidine in Treating Sleep Disorders with Comorbid Depression - Ding Y; Wang Z; Huang J; Yi Y; Wu Z (Neuropsychiatric Disease and Treatment)
Yitong Ding,1,* Zhengye Wang,1,* Jing Huang,1 Yanzi Yi,1 Zhouquan Wu2 1Department of Anesthesiology, Nanjing Medical University, Jiangning, Nanjing, 211166, People’s Republic of China; 2Department of Anesthesiology, The Second People’s Hospital of Changzhou, The Third Affiliated Hospital of Nanjing Medical University, Changzhou, Jiangsu, 213164, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhouquan Wu, Department of Anesthesiology, The Second People’s Hospital of Changzhou, The Third Affiliated Hospital of Nanjing Medical University, No. 68, Ge Hu Middle Road, Changzhou, Jiangsu, 213164, People’s Republic of China, Email wuzhouquan2005@126.comPurpose: Although Dexmedetomidine (DEX) can induce sleep that resembles natural sleep, it has demonstrated limited efficacy in patients with comorbid insomnia and depression. On the other hand, Esketamine (ESK) has shown a potent antidepressant effect. Herein, we aimed to establish whether esketamine could enhance the therapeutic efficacy of DEX in treating patients with comorbid insomnia and depression.Methods: We recruited 84 patients with comorbid insomnia and depression who were randomized into two groups for a 1-month follow-up study: the DE group (receiving dexmedetomidine and esketamine) and the DS group (receiving dexmedetomidine and saline). Outcome measures included polysomnographic monitoring (PSG), Montgomery-Åsberg Depression Rating Scale (MADRS), Pittsburgh Sleep Quality Index (PSQI), Sleep Numeric Rating Scale (SNRS), and serum brain-derived neurotrophic factor (BDNF) concentrations. The primary outcome was a comparison of PSG parameters recorded at baseline (D0) and on treatment day 3 (D3).Results: After 3 days of treatment, patients in DE group had a significant increase in total sleep duration, duration and proportion of N3 sleep (P < 0.05), a significant decrease in proportion of N2 sleep and proportion of REM sleep (P < 0.05), and a significant decrease in depression score and sleep numeric rating scale score (P < 0.05), as compared with DS group. Improvements in sleep were associated with improvements in MADRS score and increases in BDNF. Oral dryness was the most frequent adverse event (AE).Conclusion: When combined with ESK, DEX improved patients’ depression scores, further extended total sleep time, increased the N3 sleep proportion, and enhanced deep sleep continuity, with few AEs.Keywords: insomnia, depression, esketamine, dexmedetomidine, polysomnography